Identified ambivalence: When cognitive conflicts can help individuals overcome cognitive traps. - Guarana, Cristiano L.; Hernandez, Morela (Journal of Applied Psychology, 2016)
In this article we investigate the functional effects of ambivalence on decision-making processes. We build on the misattribution literature and recent work on ambivalence to propose that individuals who properly identify the causes of their ambivalence (i.e., identified ambivalence) can systematically process relevant situational cues to make more effective decisions. The results of 4 studies demonstrate that individuals experiencing identified ambivalence are less influenced by cognitive biases (i.e., the framing effect, availability bias, and conjunction bias) than individuals experiencing no ambivalence or felt ambivalence. Notably, we find that contextual awareness accounts for the effect of identified ambivalence on decision effectiveness. We then investigate the role of trait self-control as a specific contingency in our model; our results indicate that identified ambivalence leads to effective decisions when individuals are low in trait self-control. Taken together, we advance theory and offer robust, consistent empirical evidence that explains why and how ambivalence can result in functional outcomes. (PsycINFO Database Record